Delineating apathy profiles in Huntington's disease with the short-Lille Apathy Rating Scale. (December 2022) - De Paepe, Audrey E.; Garcia-Gorro, Clara; Martinez-Horta, Saül; Perez, Jesus Perez; Kulisevsky, Jaime; Rodriguez-Dechicha, Nadia; Vaquer, Irene; Subira, Susana; Calopa, Matilde; Santacruz, Pilar; Muñoz, Esteban; Mareca, Celia; et al.
Abstract: Introduction: Apathy, a prevalent feature in neurological disorders including Huntington's disease (HD), is characterized by a reduction in goal-directed behavior across cognitive, auto-activation (i.e., self-activating thoughts/behavior), and emotional domains. Nonetheless, current diagnostic criteria are incapable of distinguishing multidimensional apathy profiles. Meanwhile, the short-Lille Apathy Rating Scale (LARS-s) bears potential as an operative diagnostic tool to disentangle apathy dimensions in clinical practice. The present study thereby examines the psychometric properties and factor structure of the LARS-s to tap into apathy profiles and their underlying neural correlates in HD. Methods: Forty HD individuals were scanned and evaluated for apathy using the LARS-s, assessed for reliability and validity in HD, and the short-Problem Behavior Assessment (PBA-s). To study the dimensional structure of apathy, principal component analysis (PCA) of the LARS-s was implemented. Resulting factors were associated with gray matter volume through whole-brain voxel-based morphometry. Results: The LARS-s demonstrated satisfactory psychometric properties, sharing convergent validity with PBA-s apathy and discriminant validity against depression. PCA resulted in three factors representative of apathy profiles across cognitive, auto-activation, and emotional domains. Anatomically, global apathy was significantly related with large-scale motor, cognitive, and limbic networks. Exploratory analyses of apathy profiles revealed correspondence between each factor and distinct cortical and subcortical nodes. Conclusion: The LARS-s is capable of capturing the multidimensional spectrum of apathy. At the same time, apathy profiles in HD are underpinned by functionally diverse neural networks. Such findings promote the continued study of apathy domains to pinpoint personalized therapeutic targets in neurologic disorders in addition to HD. Highlights: The LARS-s is valid and reliable in Huntington's disease in the clinical context. The LARS-s can delineate cognitive, auto-activation, and emotional apathy domains. Subdomains are related to gray matter nodes across functionally distinct circuits.